Characterizing frost damages of concrete with flatbed scanner. (15th January 2016) - Wang, Zhendi; Zeng, Qiang; Wang, Ling; Li, Kefei; Xu, Shilang; Yao, Yan
Highlights: Flatbed scanner was developed for high quality digital image acquisition. Imaging-analysis parameters were extracted from flatbed-scanned images. Conventional parameters were measured for damage evolution. Flatbed scanner method has potential application aspects of concrete engineering. Abstract: Flatbed scanner is a low cost, fast, easy to operate, and efficient device for high quality digital image acquisition. The present study extended the applications of flatbed scanners from conventional air void counting to pore structure characterization of concrete affected by freezing–thawing (F–T) action. Imaging-analysis parameters (specific area and roundness of pores, density and length of cracks, and fractal dimension of pore outlines) were extracted from flatbed-scanned images, and conventional parameters (dynamic elastic modulus, mass and Cl − diffusion coefficient) were measured after every 25 F–T cycles. Both the imaging-analysis parameters and the conventional parameters varied with increasing F–T cycle. The successful use of a flatbed scanner to detect changes in concrete pore structure with frost damage in this research increases the expectation of its application to more aspects of concrete engineering.